(untitled) (London Journal of Medical and Health Research, 2023)
Melorheostosis is a rare congenital bone disorder present with insidious onset of bone pain. Diagnosing this rare condition and managing it is difficult. Knowledge of this rare entity is important for the physician who is treating patients with musculoskeletal pain. Case Report A 25-year-old female with right leg pain for a two-year duration. She has been seen by a lot of physicians and could not have been managed properly. Her radiographs were showing hyperostotic left ulna and right tibia. Sinister pathologies were excluded using MRI and biopsy. Her symptoms settled with intravenous Zoledronate. Pain recurred after two years and she responded well after repeated Zoledronate injection. Conclusion Though there are no key clinical features, diagnostic tests, or cause of this clinical condition, symptomatic management is adequate to manage patients with this clinical condition. Intravenous Zoledronic acid is an option for patients who have severe and resistant symptoms.